PRODUCTIVITY AND ITS DETERMINANTS IN BRAZILIAN STATES: AN ANALYSIS FROM 2010 TO 2018 - Rodrigues da Silva, Renilson (2024)
This article aims to identify and analyze some determinants of Total Factor Productivity (TFP) between Brazilian states. The analysis is carried out for the period from 2010 to 2018. For this purpose, the aggregated TFP is estimated by applying the Solow model. From the PTF, the Panel Corrected Standard Errors (PCSE) method is used, testing variables related to foreign trade, infrastructure, Government, and education as determinants. PTF for Brazil had negligible growth in the period. However, some states stood out in efficiency, such as Mato Grosso, Mato Grosso do Sul, Piauí and Maranhão. In them, agricultural production has greater relevance. As for the determinants of TFP, education is the most important variable, accounting for most of the positive variations. Highways affect the TFP positively, but on the other hand, the vehicle fleet negatively. Foreign trade is of great importance, with positive effects. The Government, in turn, affects the TFP negatively, suggesting the inefficiency of spending.